Pediatric Emergency Department Utilization and Reliance by Insurance Coverage in the United States. (16th October 2017) - Schlichting, Lauren E.; Rogers, Michelle L.; Gjelsvik, Annie; Linakis, James G.; Vivier, Patrick M.
Abstract: Objectives: For many children, the emergency department (ED) serves as the main destination for health care, whether it be for emergent or nonurgent reasons. Through examination of repeat utilization and ED reliance (EDR), in addition to overall ED utilization, we can identify subpopulations dependent on the ED as their primary source of health care. Methods: Nationally representative data from the 2010 to 2014 Medical Expenditure Panel Survey were used to examine the annual ED utilization of children age 0 to 17 years by insurance coverage. Overall utilization, repeat utilization (two or more ED visits), and EDR (percentage of all health care visits that occur in the ED) were examined using multivariate models, accounting for weighting and the complex survey design. High EDR was defined as having > 33% of outpatient visits in a year being ED visits. Results: A total of 47, 926 children were included in the study. Approximately 12% of children visited an ED within a 1‐year period. A greater number of children with public insurance (15.2%) visited an ED at least once, compared to privately insured (10.1%) and uninsured (6.4%) children. Controlling for covariates, children with public insurance were more likely to visit the ED (adjusted odds ratio [aOR] = 1.55, 95% confidence interval [CI] = 1.40–1.73) than children with private insurance, whereas uninsured children were less likely (aOR = 0.64, 95% CI = 0.51–0.81). Children age 3 and under were significantly more likely to visit the ED than children age 15 to 17, whereas female children and Hispanic and non‐Hispanic other race children were significantly less likely to visit the ED than male children and non‐Hispanic white children. Among children with ED visits, 21% had two or more visits to the ED in a 1‐year period. Children with public insurance were more likely to have two or more visits to the ED (aOR = 1.53, 95% CI = 1.19–1.98) than children with private insurance whereas there was no significant difference in repeat ED utilization for uninsured children. Publicly insured (aOR = 1.70, 95% CI = 1.47–1.97) and uninsured children (aOR = 1.90, 95% CI = 1.49–2.42) were more likely to be reliant on the ED than children with private insurance. Conclusions: Health insurance coverage was associated with overall ED utilization, repeat ED utilization, and EDR. Demographic characteristics, including sex, age, income, and race/ethnicity were important predictors of ED utilization and reliance.